Zmierzchy Bolesława Leśmiana = Twilight of Bolesław Leśmian - Cieślak, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is an attempt to analyze six short poems by BolesławLeśmian, devoted to the theme of twilight. Twilight, eagerly recalled in Romantic and Young Poland`s poetry, is for Leśmian a motive for telling stories both about impermanent love and triggering reflections of an existential nature: about the impermanence of existence and incessant passing.
Keywords: liryka polska; modernizm; Leśmian, Bolesław (1877-1937); motyw literacki; zmierzch; 20 w.; literary motif; twilight; modernism